Evaluation of tangerine hybrid resistance to Alternaria alternata - de Souza, Marcelo Claro [UNESP]; Stuchi, Eduardo Sanches; de Goes, Antonio [UNESP] (Elsevier B.V., 2009)
The Alternaria Brown Spot, caused by Alternaria alternata, is a major fungal disease in some kinds of tangerines, tangor, mandarins and pomelos. In Brazil as well as worldwide, A. alternata can cause necrosis in fruits, branches and leaves, causing substantial profit loss. In the present research, in laboratory conditions and in the field, we evaluated the resistance to the fungus, in leaves and fruits, for 22 varieties and hybrids of tangerines. To this end, we evaluated genotypes belonging to the Germplasm Bank of the Estacao Experimental de Citricultura de Bebedouro. The resistant genetic materials (found in leaves and fruits) represented four varieties of clementines (Citrus clementina); six varieties of mandarins (two belonging to C. reticulata, two to C. tangerina, one to C. deliciosa and one to C. nobilis); one tangelo (C. tangerina x C. paradisi); two mandarin hybrids (one resulting from crossing C nobilis x C. deliciosa and the other from crossing C. clementina x C. reticulata); one tangor hybrid (C. clementina) and two satsuma hybrids (C. unshiu x C. deliciosa). We also determined a relation between the inoculation of leaves and fruits. The resistance and susceptibility following inoculation in leaves and fruits supports a relationship between these organs and the physiological responses observed for the evaluated genotypes. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Citrus sp.; Alternaria brown spot; Varietal resistance